TYPES AND TECHNIQUES OF GRUNT FOR PAINTING WORKS - Avazjon Abdumajitov (Web of Journals Publishing, 2024)
This article describes the concept of painting,the types and techniques of grunt for painting works
Keywords: painting, grunt, glue grunt, cozein,zinc, emulsion grunt.